Claroideoglomus etunicatum affects the diversity and composition of the rhizosphere microbial community to help tall fescue resist saline–alkali stress - Liu, Hui; Song, Xiliang; Zhang, Peiliang; Liu, Lu; Li, Chunhua (Frontiers in Microbiology, 2026)
IntroductionArbuscular mycorrhizal fungi (AMF) and plant rhizosphere microbes reportedly enhance plant tolerance to abiotic stresses and promote plant growth in contaminated soils. Soil salinization represents a severe environmental problem. Although the influence of AMF in the phytoremediation of saline–alkali soils has been fully demonstrated, the underlying interactive mechanisms between AMF and rhizosphere microbes are still unclear.MethodsA greenhouse pot experiment was conducted to explore the effects of AMF (Claroideoglomus etunicatum) on tall fescue growth promotion and the rhizosphere microbial community in saline–alkali soils. We aimed to investigate the mechanism of AMF affecting plant growth under saline–alkali stress conditions via interactions with rhizosphere microbes.ResultsWe found that AMF significantly increased plant shoot, root, and total biomass in saline–alkali stress soil. AMF significantly increased the diversity of bacterial and fungal communities and altered their composition. For bacteria, the AMF inoculation treatment (M+) showed higher relative abundance of Proteobacteria, Actinobacteriota, and Firmicutes and lower relative abundance of Acidobacteriota and Chloroflexi compared to the no-AMF application treatment (M−). For fungi, the M+ treatment showed lower relative abundance of Ascomycota and higher relative abundance of Mortierellomycota compared to the M− treatment. Furthermore, structural equation modeling (SEM) revealed that AMF promoted plant growth under saline–alkali stress conditions mainly by regulating the diversity of bacterial communities in the rhizosphere soil.DiscussionThis study provides a theoretical basis for improving plant adaptation to saline–alkali stress through soil microbial management practices.